Programa Minha Casa Minha Vida: uma análise da política habitacional para a população de baixa renda no Brasil - Martins, Adriano Ribeiro (2015)
This paper analyzes the housing policy for low-income population in Brazil, with emphasis on the My House My Life Program (PMCMV). It also analyzes the main programs of Fernando Collor de Mello and Itamar Franco until Dilma Rousseff´s governments (1990-2014) in order to eliminate the deficit of the sector, remembering that for 2015, the Brazilian Government estimates to build 3 million of new affordable housing in urban areas, with funds from the FGTS programs and differentiated interest rate for low-income families